The relationship between shared decision-making and health-related quality of life among patients in Hong Kong SAR, China - XU, RICHARD H.; CHEUNG, ANNIE W. L.; WONG, ELIZA L. Y. (International journal for quality in health care, 2017)
To elucidate the association between health-related quality of life and shared decision-making among patients in Hong Kong after adjustment for potential confounding variables. A telephone survey was conducted with patients attending all public specialist outpatient clinics in Hong Kong between July and December 2014. The Specialist Outpatient Patient Experience Questionnaire and EQ-5D questionnaire were used to evaluate shared decision-making and quality of life, respectively. We performed a Tobit regression analysis to examine the associations between shared decision-making and quality of life after adjustment for known social, economic and health-related factors. Twenty-six of the Hospital Authority's specialist outpatient clinics. Patients aged 18 years or older who attended one of the Hospital Authority's specialist outpatient clinics between July and November 2014. Shared decision-making and quality of life score. Overall, 13 966 patients completed the study. The group reporting partial involvement in decision-making had slightly higher EQ-5D scores than the 'not involved' group and the 'fully involved' group. EQ-5D scores were higher among subjects who were younger, male, and had a higher level of education. Respondents living alone and living in institutions scored lower on the EQ-5D than patients living with families. Important differences in the relationship between the attitudes towards shared decision-making and quality of life were identified among patients. These associations should be taken into consideration when promoting patient-centred care and improving health professional-patient communication.